EFFECT OF REPLACEMENT OF FEED ADDITIVE ANTIBIOTIC WITH DIFFERENT LEVELS OF LACTIC ACID ON BROILER PERFORMANCE - Nadira Khalid, T.N. Pasha, A. Khalique and S.A. Khanl (Pakistan Veterinary Journal, 2002)
The study was conducted to ascertain the effect of replacement of feed additive antibiotic i.e. tlavomycin with different levels of lactic acid, on broiler performance. Two hundred day-old broiler chicks were random.ly divided into five groups A, B, C, D and E, with 40 chicks in each group. Lactic acid, 1, 2 and 3% was supplemented in the rations for groups B, C and D, respectively. Flavomycin was supplemented in feed for group £ and group A was a control group. Growth rate, feed intake, feed efficiency, mortality and economics were recorded. The results showed that during the starter phase, none of the supplementation of ration helped in improving feed intake, the birds of groups A and E gained maximum weight (P<0.05) and showed better FCR (P<0.05). During finisher phase, tlavomycin and 3% lactic acid supplementations helped in improving feed intake and weight gain (P<05) and all the supplementations showed better FCR than the control ration (P<0.05). Flavomycin proved to be the only economical supplementation as compared to the other rations.